Impact of On-campus Alternative Training in Clinical Practice on Postgraduate Clinical Competence - YOKOYAMA, Daiki; OTANI, Tomohiro; YOSHIDA, Toshiya; OTSUKA, Toshifumi; USUDA, Shigeru (Rigaku ryoho kagaku, 2022)
[Purpose] The purpose of this study was to compare the post-graduate clinical ability of physical therapists who received clinical training at a medical facility with those who had it replaced with on-campus training. [Participants and Methods] The subjects were 51 physical therapists who graduated from a 4-year school in 2020. Clinical performance was measured using the Clinical Competence Evaluation Scale in Physical Therapy (CEPT). The group who received the clinical training was designated as the regular training group, and the group who received the on-campus training was designated as the alternative training group. [Results] There was no significant difference in the total CEPT score, but the alternative training group showed significantly lower values in “knowledge of clinical physical therapy” and “self learning abilities”. [Conclusion] It was found that the physiotherapists who had clinical training replaced with on-campus training tended to be disadvantaged in clinical knowledge and self learning.